The production and utilization of GDP-glucose in the biosynthesis of trehalose-6-phosphate by Streptomyces venezuelae - Asención Diez, Matías Damián (2017)
Trehalose-6-phosphate synthase OtsA from streptomycetes is unusual in that it uses GDP-glucose as the donor substrate rather than the more commonly used UDP-glucose. We now confirm that OtsA from Streptomyces venezuelae has such a preference for GDP-glucose and can utilize ADP-glucose to some extent too. A crystal structure of the enzyme shows that it shares twin Rossmann-like domains with the UDP-glucose-specific OtsA from Escherichia coli. However, it is structurally more similar to Streptomyces hygroscopicus VldE, a GDP-valienol-dependent pseudoglycosyltransferase enzyme. Comparison of the donor binding sites reveals that the amino acids associated with the binding of diphosphoribose are almost all identical in these three enzymes. By contrast, the amino acids associated with binding guanine in VldE (Asn, Thr, and Val) are similar in S. venezuelae OtsA (Asp, Ser, and Phe, respectively) but not conserved in E. coli OtsA (His, Leu, and Asp, respectively), providing a rationale for the purine base specificity of S. venezuelae OtsA. To establish which donor is used in vivo, we generated an otsA null mutant in S. venezuelae. The mutant had a cell density-dependent growth phenotype and accumulated galactose 1-phosphate, glucose 1-phosphate, and GDP-glucose when grown on galactose. To determine how the GDP-glucose is generated, we characterized three candidate GDP-glucose pyrophosphorylases. SVEN_3027 is a UDP-glucose pyrophosphorylase, SVEN_3972 is an unusual ITP-mannose pyrophosphorylase, and SVEN_2781 is a pyrophosphorylase that is capable of generating GDP-glucose as well as GDP-mannose. We have therefore established how S. venezuelae can make and utilize GDP-glucose in the biosynthesis of trehalose 6-phosphate.